2004
DOI: 10.1088/0953-4075/37/7/057
|View full text |Cite
|
Sign up to set email alerts
|

Loss and revival of phase coherence in a Bose–Einstein condensate moving through an optical lattice

Abstract: We investigate the phase coherence of a trapped Bose-Einstein condensate that undergoes a dynamical superfluid-insulator transition in the presence of a one-dimensional optical lattice. We study the evolution of the condensate after a sudden displacement of the harmonic trapping potential by solving the Gross-Pitaevskii equation, and comparing the results with the prediction of two effective 1D models. We show that, owing to the 3D nature of the system, the breakdown of the superfluid current above a critical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…For each p, the order parameter p0 ͑r , z͒ and its energy E p are calculated by solving the stationary GP equation by means of iterative methods. Then the Bogoliubov equations (12) and (13) are transformed into matrix equations by projecting the functions u and v on the Bessel-Fourier basis ͉l , n͘ϵJ 0 ͑␣ 0n r / r max ͒exp͑i2q B lz͒, where ␣ 0n are zeros of the Bessel functions J 0 ͑r͒ and r max is the radius of the computational box [18,19]. The resulting equations are not diagonal over the Fourier index l, and involve the numerical diagonalization of a 2 ϫ N r ϫ N z rank matrix.…”
Section: ͑16͒mentioning
confidence: 99%
See 3 more Smart Citations
“…For each p, the order parameter p0 ͑r , z͒ and its energy E p are calculated by solving the stationary GP equation by means of iterative methods. Then the Bogoliubov equations (12) and (13) are transformed into matrix equations by projecting the functions u and v on the Bessel-Fourier basis ͉l , n͘ϵJ 0 ͑␣ 0n r / r max ͒exp͑i2q B lz͒, where ␣ 0n are zeros of the Bessel functions J 0 ͑r͒ and r max is the radius of the computational box [18,19]. The resulting equations are not diagonal over the Fourier index l, and involve the numerical diagonalization of a 2 ϫ N r ϫ N z rank matrix.…”
Section: ͑16͒mentioning
confidence: 99%
“…4 where we plot the real and imaginary parts of the eigenfrequencies obtained by solving Eqs. (12) and (13) in the case p / q B = 0.55. Finally, as one can see in the last two frames of Fig.…”
Section: ͑16͒mentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses based on the Gross-Pitaevskii (GP) equation have elucidated that the density modulation is formed as a result of the complicated mode mixing in momentum space. 21,22 On the other hand, Mun et al 11 experimentally determined the phase boundary of dynamical instability in a wide range of interactions using a BEC in a 3D moving optical lattice. Here, * E-mail address: asaoka@olive.apph.tohoku.ac.jp the system is described using the Bose-Hubbard (BH) model at low fillings and far from that observed in the experiment by Fallani et al It was demonstrated that the measured results are in good agreement with the stability phase diagram of the BH model obtained by the dynamical Gutzwiller approximation.…”
Section: Introductionmentioning
confidence: 99%